Fetal MRI-based Mediastinal Shift Angle (MSA) and percentage Area of Left Ventricle (pALV) as prognostic parameters for congenital diaphragmatic hernia - Thater, Greta; Angermann, Lara; Virlan, Silviu-Viorel; Weiß, Christel; Rafat, Neysan; Boettcher, Michael; Elrod, Julia; Bayer, Tom Walter; Nowak, Oliver Claudius; Schönberg, Stefan; Weis, Meike (Journal of Clinical Medicine, 2024)
Objective: Fetal magnetic resonance imaging (MRI) is broadly used as a method for assessing prognosis in congenital diaphragmatic hernia (CDH). In addition to the extent of lung hypoplasia, determined by measuring the lung volume, cardiac impairment due to pulmonary hypertension and left cardiac hypoplasia is decisive for the prognosis. The percentage area of left ventricle (pALV) describes the percentage of the inner area of the left ventricle in relation to the total area, whereas the mediastinal shift angle (MSA) quantifies the extent of cardiac displacement. The prognostic value of pALV and MSA should be evaluated in terms of survival, the need for extracorporeal membrane oxygenation (ECMO) therapy, and the development of chronic lung disease (CLD). Methods: In a total of 122 fetal MRIs, the MSA and pALV were measured retrospectively and complete outcome parameters were determined regarding survival for all 122 subjects, regarding ECMO therapy in 109 cases and about the development of CLD in 78 cases. The prognostic value regarding the endpoints was evaluated using logistic regression and ROC analysis. Results: The MSA was significantly higher in children who received ECMO therapy (p = 0.0054), as well as in children who developed CLD (p = 0.0018). ROC analysis showed an AUC of 0.68 for ECMO requirement and 0.77 with respect to CLD development. The pALV showed a tendency towards higher levels in children who received ECMO therapy (p = 0.0824). The MSA and the pALV had no significant effect on survival (MSA: p = 0.4293, AUC = 0.56; pALV: p = 0.1134, AUC = 0.57). Conclusions: The MSA determined in fetal MRI is a suitable prognostic parameter for ECMO requirement and CLD development in CDH patients and can possibly be used as a supplement to the established parameters.
Gesehen am 21.02.2024